Cutaneous desmoid‐type fibromatosis: A rare case with molecular profiling. (30th June 2021) - Aghighi, Maryam; Cloutier, Jeffrey M.; Hoover, William D.; Roy, Katherine; Lo, Amy A.; Brown, Ryanne A.
Abstract: Fibromatoses encompass a broad group of histopathologically similar fibroblastic/myofibroblastic proliferations with divergent clinical manifestations and behavior. Deep (desmoid‐type) fibromatoses are typically large, rapidly growing, and locally aggressive tumors that occur in the abdominal wall, mesentery, and extra‐abdominal soft tissue, principally the musculature of the trunk and extremities. Most sporadic cases of desmoid fibromatosis harbor inactivating mutations in CTNNB1, the gene encoding beta‐catenin. Tumors occurring in the context of familial adenomatous polyposis and Gardner syndrome bear inactivating mutations in APC . By contrast, mutations in CTNNB1 or APC have not been identified in cases of superficial fibromatosis. Cutaneous involvement by desmoid fibromatosis is exceedingly rare. Here we present a 78‐year‐old male with desmoid‐type fibromatosis arising in the dermis of the right medial calf with a pathogenic mutation in CTNNB1 and a variant of unknown significance in APC .